Modernizing the World Health Organization List of Essential Medicines for Preventing and Controlling Cardiovascular Diseases - Kishore, Sandeep P; Blank, Evan; Heller, David J; Patel, Amisha; Peters, Alexander; Price, Matthew; Vidula, Mahesh; Fuster, Valentin; Onuma, Oyere; Huffman, Mark D; Vedanthan, Rajesh (Journal of the American College of Cardiology, 2018)
The World Health Organization (WHO) Model List of Essential Medicines (EML) is a key tool for improving global access to medicines for all conditions, including cardiovascular diseases (CVDs). The WHO EML is used by member states to determine their national essential medicine lists and policies and to guide procurement of medicines in the public sector. Here, we describe our efforts to modernize the EML for global CVD prevention and control. We review the recent history of applications to add, delete, and change indications for CVD medicines, with the aim of aligning the list with contemporary clinical practice guidelines. We have identified 4 issues that affect decisions for the EML and may strengthen future applications: 1) cost and cost-effectiveness; 2) presence in clinical practice guidelines; 3) feedback loops; and 4) community engagement. We share our lessons to stimulate others in the global CVD community to embark on similar efforts.